MEMPERTEGAS VISI PENDIDIKAN ISLAM SEBAGAI PENDIDIKAN MULTIKULTURAL - Fathonah, Siti (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2020)
Abstract: Indonesia is a compound country. The diversity of the Indonesian nation on the one hand is a treasure that should be maintained and provide dynamics for the nation, but on the other hand can also be a source of disputes and conflicts. This research uses the hermeneutic method with a philosophical approach. The concept of multicultural Islamic religious education is a division of the concept of multicultural, religious education needs to use the multicultural paradigm as the main foundation for teaching and learning. Multicultural Islamic education is very important because it offers a role model of education that specifically introduces multiculturalism that is beneficial for the inculcation of inclusivemulticulturalistic Islamic values in Indonesia. Abstrak: Indonesia adalah negara majemuk. Keragaman bangsa indonesia disatu sisi merupakan suatu khazanah yang patut dipelihara dan memberikan dinamika bagi bangsa, namun disisi lain dapat pula menjadi sumber perselisihan dan konflik. Penelitian ini dengan menggunakan metode hermeneutik dengan pendekatan filosofis. Konsep pendidikan agama Islam multikultural merupakan devisi dari konsepnya tentang pendidikan agama berwawasan multikultural perlu menggunakan paradigma multikultural sebagai landasan utama penyelenggaraan belajar mengajar. Pendidikan islam multikultural keberadaanya sangat penting lantaran menawarkan role model pendidikan yang secara spesifik mengintrodusisasi multikulturalisme yang bermanfaat bagi penanaman nilai-nilai islam yang inklusifmultikulturalistik di Indonesia.